Young Human Resource Development to Support Village SDGs - Shade Rahmawati; Mukhtasor Mukhtasor; Agoes Pratikto; Sujantoko Sujantoko; Haryo Dwito Armono; Wisnu Wardhana; Muhammad Zikra; Hasan Ikhwani; Rudi Walujo Prastianto (IPTEK Journal of Proceedings Series, 2023)
All states have different histories, cultures and local wisdom which then influence how the Sustainable Development Goals (SDGs) are applied to their development plan. The specific characters of Indonesian villages leads the government to establish the 18th SDGs called Village SDGs in 2020. The Village SDGs program emphasizing one message: no one left behind. In relation to this, the roles of young human resources in order to succeed the bottom-to- top development in the villages are crucial. In an effort to develop the village, the community, especially the youth, must not lose their identity. Following those condition, a community service program regarding young human resource development has been executed in partnership with Youth Information and Counseling Center (or Pusat Informasi dan Konseling Remaja) of Krecek Village, Kediri Regency. The development program is concentrating on the basic understanding of their role in society, moral values, adolescent health and family functioning. Two- days coaching which involves Family Planning Counseling Center (or Balai Penyuluhan KB) and Bureau of Population Control, Family Planning, Women's Empowerment and Child Protection (DP2KBP3A) of Kediri Regency was held as the first step. Evaluation regarding further needs from the participants are being obtained.